Hubungan Sumber Air Minum dengan Kejadian Penyakit Gastrointestinal - Ayu Novitrie; Frisca Rahmadina; Widya Ayu Pratiningsih; Dwi Fitriani (Buletin Keslingmas, 2025)
Access to safe drinking water remains a critical public health concern in many peri-urban areas of Indonesia. Gastrointestinal diseases continue to be prevalent in these regions, potentially linked to water quality and sources. Understanding this relationship is essential for developing targeted interventions and improving community health outcomes.This study aimed to investigate the association between drinking water sources and the incidence of gastrointestinal diseases among community members within the service area of Talang Ratu Primary Health Center in Palembang, Indonesia. A cross-sectional study was conducted involving 37 community members at the Bougenville Posyandu (integrated health post). Data were collected through structured questionnaires and direct observation. Chi-square analysis was used to examine the association between variables with a significance level of p < 0.05.The majority of respondents (81.1%) used groundwater, rainwater, or processed piped water, while only 18.9% consumed refillable or bottled water. Gastrointestinal symptoms were reported by 37.8% of participants. Statistical analysis revealed no significant association between drinking water source and gastrointestinal disease incidence (p = 1.000).This study found that drinking water source alone was not significantly associated with gastrointestinal disease incidence in this peri-urban community. Multiple factors beyond water source likely influence disease transmission, including water treatment practices, hygiene behaviors, and environmental conditions. Comprehensive approaches addressing these multiple determinants are recommended for effective prevention of gastrointestinal diseases.